LATE GLACIAL TO HOLOCENE PALEOENVIRONMENTAL EVOLUTION OF THE BLACK SEA, RECONSTRUCTED WITH STABLE OXYGEN ISOTOPE RECORDS OBTAINED ON OSTRACOD SHELLS - Bahr A.; Wefer G.; Arz H.W.; Lamy F. (My University, 2006)
High-resolution stable oxygen isotope (δ18O on ostracod shells), XRF-scanning and bulk grain-size data obtained on a transect of 6 gravity cores from the continental slope in the northwestern Black Sea give new insight into the hydrological evolution of the Black Sea since the Last Glacial Maximum (LGM). Stable climatic conditions during the LGM were followed by a series of meltwater pulses between 18 and 15.5 kyr BP that resulted in temporary isotopic depletion of the Black Sea waters. Subsequently, steadily increasing δ18O values in all cores are mainly caused by isotopically enriched precipitation at the onset of the Allerød/ølling warm period. A comparison of the major trends in δ18O at different water depths suggests evaporation-driven deep water formation since ~14.5 kyr BP, while the two shallowest cores from 168 and 465 m water depth were under the influence of increased warming in the upper water column since 14.5 and 12.5 kyr BP, respectively. The core from 168 m depth seems to be additionally influenced by freshwater input of the Danube. This core provides a high-resolution record from the Younger Dryas/Allerød boundary and suggests that a NAO-like climate mode was governing the interannual variability in the run-off of the Danube, which implies that this climate mode has been a persistent climatic feature over central Europe. The inflow of saline Mediterranean waters occurs between 9 and 8 kyr BP, where a merging of all δ18O records signals an initial homogenisation of the water column. © 2005 Elsevier B.V. All rights reserved.
Keywords: BLACK SEA; LATE GLACIAL; NAO; OSTRACODS; OXYGEN ISOTOPES; PALEOHYDROLOGY; Кайнозой::Четвертичная::Голоцен; Cenozoic::Quaternary::Holocene